Risk Identification and Management Analysis at Company X Using FMEA and EPQ Methods - Islami, Mega Cattleya P. A; Rahadian, Yanuar Rafi Rahadian; Bisri, Hasan; Winursito, Yekti Condro (UPN Veteran Jatim, 2024)
This study aims to identify and manage risks in Company X’s instant noodle production process using Failure Mode and Effects Analysis (FMEA) and Economic Production Quantity (EPQ) methods. FMEA is used to analyze potential failure modes, while EPQ optimizes production quantities to minimize storage and overproduction costs. The research identifies key risks such as overproduction, machinery failures, and packaging defects. Data collected includes production volumes, raw material usage, and defect rates. FMEA reveals that overproduction is the primary risk, leading to high storage costs. EPQ calculations are performed to determine the optimal monthly production for three instant noodle variants, resulting in significant cost savings. The study concludes that implementing EPQ alongside FMEA minimizes risks and reduces inventory management costs, highlighting the importance of systematic risk management in production optimization. This approach helps Company X enhance efficiency while cutting purchasing and costs expenses by Rp. 3,900,000.00 per month.